2016
DOI: 10.3892/ijo.2016.3658
|View full text |Cite
|
Sign up to set email alerts
|

A novel polysaccharide derived from algae extract induces apoptosis and cell cycle arrest in human gastric carcinoma MKN45 cells via ROS/JNK signaling pathway

Abstract: In recent years, interest in biological activities of compounds from marine organisms has intensified. Cancer is the most principal enemy for human life and health. For the first time, to the best of our knowledge, we investigated a novel algae-derived polysaccharide for its role in inducing apoptosis and cell cycle arrest in human gastric carcinoma MKN45 cells. We found that the novel polysaccharide suppressed MKN45 cell proliferation, induced cell apoptosis and arrested the cells at G2/M phase. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 33 publications
4
17
0
Order By: Relevance
“…We investigated the pharmacological effects of HTE on HSCs using multiple approaches and found that it induces apoptosis through ROS production via the p38, JNK, and caspase‐3‐dependent pathways. Many studies have demonstrated the role of HSC activation in liver fibrosis and have highlighted the significance of HSC‐induced apoptosis in the pathogenesis of liver fibrosis (Friedman, ; Issa et al, ; Jia et al, ; Kuo et al, ; Mederacke et al, ; Puche et al, ; von Schwarzenberg & Vollmar, ; Xie, Fujii, Zhao, Shinohara, & Matsukura, ). Therefore, we hypothesize that hsian‐tsao may potently inhibit HSC viability through ROS production via the JNK and p38 MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the pharmacological effects of HTE on HSCs using multiple approaches and found that it induces apoptosis through ROS production via the p38, JNK, and caspase‐3‐dependent pathways. Many studies have demonstrated the role of HSC activation in liver fibrosis and have highlighted the significance of HSC‐induced apoptosis in the pathogenesis of liver fibrosis (Friedman, ; Issa et al, ; Jia et al, ; Kuo et al, ; Mederacke et al, ; Puche et al, ; von Schwarzenberg & Vollmar, ; Xie, Fujii, Zhao, Shinohara, & Matsukura, ). Therefore, we hypothesize that hsian‐tsao may potently inhibit HSC viability through ROS production via the JNK and p38 MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Following treatment with the polysaccharide (100 μ g/ml) or SP600125 (5 μ M), MCF-7 cells (1×10 5 cells/well) were further incubated for 48 h. The cells were rinsed with serum-free medium and were incubated in 5 μ M H2-DCFDA for 60 min at 37°C. The cells were then examined under a fluorescence microscope (C1-T-SM; Nikon Corporation, Tokyo, Japan), collected and subjected to a fluorescence spectrophotometry (F-2500; Hitachi, Ltd., Tokyo, Japan) to detect the DCF fluorescence inside cells (excitation, 488 nm; emission, 521 nm) as described ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…A novel polysaccharide derived from algae extract has been previously investigated. The biological activity of this novel polysaccharide was first investigated using retinal pigment epithelial cells ( 7 ), and the effect in inhibiting human gastric carcinoma MKN45 cells was also reported recently ( 8 ). The current study aimed to determine if this extract affects other types of cancers, and the signaling pathways involved.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Micro- and macro-algal extracts have become important sources of bioactive molecules with anti-cancer properties [1,2,3,4]. Their cytotoxic effect was established for various cancer cell lines, for example, human hepatocarcinoma cell line (HepG2) [5], human breast carcinoma cell line (MCF-7) [6], but also human colon carcinoma cell lines, including Caco-2 [7,8,9].…”
Section: Introductionmentioning
confidence: 99%